2008
DOI: 10.1152/ajpheart.91496.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of gp91phox-containing NADPH oxidase in left ventricular remodeling induced by intermittent hypoxic stress

Abstract: Intermittent hypoxia due to sleep apnea syndrome is associated with cardiovascular diseases. However, the precise mechanisms by which intermittent hypoxic stress accelerates cardiovascular diseases are largely unclear. The aim of this study was to investigate the role of gp91(phox)-containing NADPH oxidase in the development of left ventricular (LV) remodeling induced by intermittent hypoxic stress in mice. Male gp91(phox)-deficient (gp91(-/-)) mice (n = 26) and wild-type (n = 39) mice at 7-12 wk of age were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 37 publications
1
45
1
Order By: Relevance
“…39,40 We also reported elevated interleukin-6, TNF-a mRNA and NF-kB-binding activity in the LV myocardium of mice exposed to intermittent hypoxia. 5,18 These results suggest that inflammatory cytokines might be involved in the LV remodeling induced by intermittent hypoxia. In this study, pitavaststin reduced the mRNA expression level of TNF-a in the LV myocardium, thereby preventing LV remodeling.…”
Section: Pitavastatin Attenuates Hypoxia-induced LV Remodeling S Inammentioning
confidence: 77%
See 4 more Smart Citations
“…39,40 We also reported elevated interleukin-6, TNF-a mRNA and NF-kB-binding activity in the LV myocardium of mice exposed to intermittent hypoxia. 5,18 These results suggest that inflammatory cytokines might be involved in the LV remodeling induced by intermittent hypoxia. In this study, pitavaststin reduced the mRNA expression level of TNF-a in the LV myocardium, thereby preventing LV remodeling.…”
Section: Pitavastatin Attenuates Hypoxia-induced LV Remodeling S Inammentioning
confidence: 77%
“…33,34 We have shown that hypoxia-induced histological degeneration was prevented in gp91 À/À mice, suggesting that gp91 phox -containing NADPH oxidase has a crucial role in the pathophysiology of intermittent hypoxia-induced LV remodeling associated with increase in oxidative stress. 5 Pitavastatin significantly reduced the plasma levels of LPO, which were increased by exposure to intermittent hypoxia, without affecting the plasma cholesterol level. Furthermore, the expression levels of 4-HNE and superoxide production in the LV myocardium were also significantly suppressed.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations